2020
DOI: 10.1192/j.eurpsy.2020.62
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interaction: New insights into perceived parenting and social anxiety among adolescents

Abstract: Abstract Background. Social anxiety symptoms (SAS) are among the most common mental health problems during adolescence, and it has been shown that parenting influences the adolescent’s level of social anxiety. In addition, it is now widely assumed that most mental health problems, including social anxiety, originate from a complex interplay between genes and environment. However, to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Possible explanations could be that childhood psychiatric disorders might be influenced by environmental or epigenetic factors [ 39 ]. The upbringing and surroundings of multiple offspring differ from those of singletons, and certain family and social factors, such as strict parenting, could contribute to these differences in environmental and epigenetic factors [ 40 ]. Additionally, while our study suggests that multiple pregnancies themselves may not increase the risk of psychiatric disorders in offspring, pregnant women with multiple pregnancies may be more susceptible to various pregnancy complications [ 41 , 42 ], some of which, such as preterm birth [ 43 ], have been associated with psychiatric disorders in offspring [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations could be that childhood psychiatric disorders might be influenced by environmental or epigenetic factors [ 39 ]. The upbringing and surroundings of multiple offspring differ from those of singletons, and certain family and social factors, such as strict parenting, could contribute to these differences in environmental and epigenetic factors [ 40 ]. Additionally, while our study suggests that multiple pregnancies themselves may not increase the risk of psychiatric disorders in offspring, pregnant women with multiple pregnancies may be more susceptible to various pregnancy complications [ 41 , 42 ], some of which, such as preterm birth [ 43 ], have been associated with psychiatric disorders in offspring [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the PWAS analysis of different gender populations, multiple candidate genes associated with PTSD were identified in the male and female populations, such as GLO1 and GSTZ1 in females and AKT3 and MAPK8IP3 in males. Among the candidate genes in the female population, the GLO1 gene was discussed in the previous passages on overlapping genes; GSTZ1 (glutathione S-transferase Zeta 1) is a member of the glutathione S-transferase super-family, responsible for glutathione-dependent metabolism and involved in the regulation of oxidative stress [ 42 ]. Previous studies have found many genetic polymorphisms in the coding and promoter regions of the GSTZ1 gene, having significant effects on the protein’s kinetic characteristics and/or its expression levels [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another related study found that polymorphisms in the GSTZ1 gene were associated with early-onset susceptibility to bipolar disorder [ 44 ]. Furthermore, a gene–environment interaction study suggested that GSTZ1 is related to genes associated with harsh punitive parenting, which may contribute to social anxiety in adolescence [ 42 ]. The possible mechanism is that this gene is involved in biological pathways that regulate oxidative stress and glutamate neurotransmission associated with anxiety-like behavior and may be sensitive to stressful life events during development.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research has demonstrated that parenting characteristics such as overprotection (Yaffe, 2021), harsh punitive control (Chubar et al, 2020), intrusive and manipulative control (Gómez-Ortiz et al, 2019), lower autonomy support (Nelemans et al, 2020), rejection (Smout et al, 2019) are also associated with social anxiety. Longitudinal studies have demonstrated that parenting behavior has an impact on the emotion regulation strategies that children with behavioral inhibition use, which in turn contributes to social anxiety outcomes (Suarez et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%